FORMATION OF CONFLICT MANAGEMENT COMPETENCE OF A UNIVERSITY TEACHER - I. V. NIKULINA; N. V. SOLOVOVA (Высшее образование в России, 2018)
This article discusses the process of formation of conflict management competence of a University teacher. The authors analyze the interpretation of the concept of “conflict management competence of a University teacher” presented in the literature. The structure of University teacher’s conflict management competence consists of interrelated components: gnostic, regulatory, design, reflexive and status, regulatory, communicative. The conditions that should be created for the development of the conflict management competence of heads of educational units, teachers to be more effective are as follows: organizational and managerial, personnel, technological, psychological, and methodical. The methods and forms to develop the conflict management competence of a University teacher include those that boost a positive motivation, interactive learning methods (role games, brainstorming, case studies, psychological training), methods aimed at creation of personal educational environment (self-reflection, assimilation of teachers’ experience, self-knowledge). The paper presents the training program “Technology of conflict management in educational institutions” aimed at the formation of the conflict management competence of heads of educational units and a special curriculum of an advanced training “Management of pedagogical conflict”designed for the formation of University teachers’ abilities of pedagogical conflicts constructive resolution.